Effect of target-substrate distance on thickness and hardness of carbon thin films on SKD11 steel using target material from battery carbon rods - Purkuncoro, Aladin Eko; Soenoko, Rudy; Santjojo, Dionysius Joseph Djoko Herry; Irawan, Yudy Surya (Eastern-European Journal of Enterprise Technologies, 2021)
Carbon thin films on SKD11 steel were deposited by 40 kHz frequency plasma sputtering technique using a waste of battery carbon rods in argon plasma, and their mechanical properties were investigated by various target-substrate distances (1 cm, 1.7 cm, 2 cm, and 2.4 cm). The power used is 340 watts, the vacuum time is 90 minutes, and the gas flow rate is 80 ml/minute. The deposition time of carbon in plasma sputtering is 120 minutes with the initial temperature (temperature during vacuum) of 28 oC and the final temperature (the temperature after plasma sputtering) is 300 oC. The hardness value of SKD11 steel deposited with carbon thin films on SKD11 with target-substrate distance was tested using the Vickers microhardness test. Testing the thickness of the carbon thin films on the SKD11 steel substrate was carried out using a Nikon type 59520 optical microscope. Qualitative analysis of the thickness of the carbon thin films on the SKD11 steel substrate at a scale of 20 μm is shown by an optical microscope. Qualitatively, the thin film at a distance of 1.7 cm looks the brightest and thickest than other distance variations. Based on the Vickers microhardness test and Nikon type 59520 optical microscope, at the distance of 1 cm to 1.7 cm, the average thickness and hardness increased from 10,724 μm (286.6 HV) to 13,332 μm (335.9 HV). Furthermore, at the variation of the distance from 1.7 cm to 2.4 cm, the average thickness and hardness continued to decrease from 13.332 μm (335.9 HV) to 7.257 μm (257.3 HV). The possibility of interrupting atoms colliding with argon atoms in inert conditions increases at a long distance, thus causing the deposition flux on the SKD11 steel substrate to decrease